(3GdcGed aj HMhK GdJShjbs - (3HOQ GdOjf(B, (3gdGds ((3YeGf(B:s (3OGQ RgQGf(B,s, 2002)
(3ebOeI h eONd Gdi HMhK GdJShjb h GdJWQb Gdi HMhK GdJShjb h GJNGP GdbQGQGJ eY JfGhd fXe GdeYdheGJ GdJShjbjI h cPG JUeje h GLQGAGJ GdHMK GdJShjbj h GSJNOGe GdeYdheGJ GdJShjbjI aj GNJjGQ GdbQGQGJ Gh GdHOGFd GdefGSHI HGSJNOGe fXQjI HjR ddbQGQGJ h GdJWQb Gdi GdJLQHI GdYdejI h GdHjGfGJ h WQb GdMUhd Ydi GdHjGfGJ GdChdjI h GdeTGgOI h GdbjGS h SdGde GdbjGS h CNjQG GdYjfGJ h GdJMdjd (B.s
(3GdeQGLY U(B.223s
Keywords: (3GdJShjb (B- (3HMhKs